Impacto de la frecuencia y hábitos de consumo de bebidas ácidas asociados al desgaste dental erosivo en los estudiantes de la UAN Villavicencio (2021)
The Dental erosion is the localized, chronic and pathological loss of the hard tissues of the teeth. This is because chemical solutions come into direct contact with the teeth; it has been proven that the diet of adolescents and adults is mostly made up of acidic foods and drinks that generate this type of condition which, if not treated in time, will seriously compromise the dental structure. In Colombia there are few studies on the prevalence of erosive dental wear, therefore, the objective of this study is to determine the relationship between the frequency and consumption habits of acidic drinks with the prevalence of dental erosion, providing important knowledge on the prevalence of this condition and seeking to create awareness among dental students and dentists already graduated to increase the focus on this condition in order to achieve its early detection.